The Development of Lectora Inspire-Based Interactive Learning on General Administration Subject - Akbarini, Nur Rahmi; Murtini, Wiedy; Rahmanto, Andre N (Fakultas Ekonomi, Universitas Negeri Semarang, 2018)
This study was a research and development type. The media developed was a lectora inspire-based interactive learning media in general administration subject. The procedure of research and development employed nine out of ten steps of Borg & Gall’s research and development (1989). Data analysis was carried out using descriptive qualitative and quantitative analyses with t-test. Considering the result of analysis on the effectiveness of lectora inspire-based interactive learning media with t-test formula, it could be found that t-statistic value obtained in posttest of experiment and control class was 5.747, with ttable of 2.000172; thus tstatitic > ttable meaning that the improvement of learning outcome in experiment class was better than that in control class. The learning outcome of experiment class showed the mean post-test of 84.53, while that of control class showed the mean posttest of 71.73. The conclusion of research was that Lectora Inspire-based interactive learning media was feasible and was used effectively to improve the students’ learning outcome. It was based on the result of t-test suggesting the significance value (0.000<0.05), indicating that there is a difference of learning outcome between experiment class and control class